Mother-child interaction: implications of chronic maternal anxiety and depression - Dib, Eloisa Pelizzon [UNESP]; Padovani, Flávia Helena Pereira [UNESP]; Perosa, Gimol Benzaquen [UNESP] (Springer Nature, 2019)
Background: The literature has few studies on the quality of the mother-child interaction when mothers suffer from chronic anxiety and depression. This study aimed to compare characteristics of the interaction between 14-month-old children and their mothers who presented symptoms of chronic anxiety or depression with those of 14-month-old children and their mothers who did not present mental problems. Method: The sample consisted of 40 mother-infant dyads selected from a prospective cohort study. They were assessed using the State-Trait Anxiety Inventory and the Beck Depression Inventory, at three time points: during pregnancy and at 6 months and 14 months of the infant’s life. Three groups were formed: 10 mothers with symptoms of chronic anxiety, 8 mothers with symptoms of chronic depression, and a control group of 22 mothers without mental health problems. The mothers responded to a socioeconomic questionnaire, and then a 7-min episode of the dyad interaction was recorded and assessed using categories indicated in a dyadic interaction assessment protocol. This consisted of six categories that evaluate the behavior of the caregiver and four categories that evaluate the child’s behavior. Results: A significantly higher percentage of mothers with chronic depressive symptoms had not completed high school and did not live with a partner. When comparing the interaction behaviors of the three groups, mothers with symptoms of chronic depression were significantly less sensitive, were more disengaged, and showed less positive affect than those in the control group. They also engaged in significantly fewer stimulations and displayed more negative affect compared with both the control group and mothers with chronic anxiety symptoms. Anxious mothers presented greater intrusiveness compared with mothers in the control group. Regarding the children, those with mothers showing symptoms of chronic depression interacted significantly less than those with mothers showing symptoms of chronic anxiety and the control group. Conclusions: The results indicate that mother-infant interaction is most severely compromised among mother-infant dyads comprised of mothers with chronic depressive symptoms, compared with dyads of mothers with chronic anxiety symptoms and dyads of control group mothers without mental health problems.
Keywords: Chronic maternal anxiety; Chronic maternal depression; Maternal mental health; Mother-child interaction